2019
DOI: 10.1101/828442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delineation of the SUMO-Modified Proteome Reveals Regulatory Functions Throughout Meiosis

Abstract: Running title: The SUMO-modified meiotic proteome 2 SUMMARY Protein modification by SUMO helps orchestrate the elaborate events of meiosis to faithfully produce haploid gametes. To date, only a handful of meiotic SUMO targets have been identified. Here we delineate a multidimensional SUMO-modified meiotic proteome in budding yeast, identifying 2747 conjugation sites in 775 targets, and defining their relative levels and dynamics. Modified sites cluster in disordered regions and only a minority match consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 141 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…We proceeded to ask whether the SUMO binding of Nse5 contributes to Nse2-dependent sumoylation. Recently, mass spectrometry-based mapping showed that Smc5 and 6 are sumoylated at their coiled-coil regions (44). In our 3D model, these sites are located close to Nse2 and the Nse5-6 complex (Fig.…”
Section: Nse5 Sumo-interacting Motifs Affect Smc5 and 6 Sumoylationmentioning
confidence: 55%
See 1 more Smart Citation
“…We proceeded to ask whether the SUMO binding of Nse5 contributes to Nse2-dependent sumoylation. Recently, mass spectrometry-based mapping showed that Smc5 and 6 are sumoylated at their coiled-coil regions (44). In our 3D model, these sites are located close to Nse2 and the Nse5-6 complex (Fig.…”
Section: Nse5 Sumo-interacting Motifs Affect Smc5 and 6 Sumoylationmentioning
confidence: 55%
“…(C) Smc5 and Smc6 sumoylation sites in the 3D model of the Smc5/6-Nse2/5/6 complex. The Smc5 and 6 sumoylation sites, including Smc5 K323 and 327 and Smc6 K343 and 350 as mapped by Bhagwat et al (44) are marked on our 3D model as green balls and indicated by arrows. (D) The sumoylation levels of Smc5 and Smc6, but not Nse4, were reduced in nse5-sim6,9 mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it will be of interest to determine the full set of factors that Mms21 acts through to exert its functions. We note that a recent analysis of the yeast meiotic SUMO proteome found SUMO conjugated to many recombination-associated proteins, including several subunits of the Smc5-Smc6-Mms21 complex (Bhagwat et al 2019).…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, it will be of interest to determine the full set of factors that Mms21 acts through to exert its functions. We note that a recent analysis of the yeast meiotic SUMO proteome found SUMO conjugated to many recombination-associated proteins, including several subunits of the Smc5-Sm6-Mms21 complex (BHAGWAT et al 2019).…”
Section: Discussionmentioning
confidence: 77%